FIBRIN AND FIBRINOGEN DEGRADATION PRODUCTS IN MALIGNANCY - RAI, RAMJI (Med J Armed Forces India, 1996)
Sixty four patients of cancer, comprising of 39 leukaemia, 8 lymphomas and 17 cases of solid tumours were included in this study. Quantitative estimation of FDP, fibrinogen and platelets were done in all. Elevated levels of FDP (≥ 10 µgm/mL) were found in 29 patients. These patients were further categorised as decompensated, overcompensated and compensated intravascular coagulation and fibrinolytic syndrome on the basis of platelet counts and fibrinogen levels.